Screening and Isolation of Associated Bioactive Microorganisms from Fasciospongia cavernosa from of Visakhapatnam Coast, Bay of Bengal. Issue 4 (2012) - Kumar, P. Shamsher; Krishna, E. Radha; Sujatha, P.; Kumar, B. Veerendra
Abstract : Nature, especially the marine environment, provides the most effective drugs used in human therapy. Among the metazoans, the marine sponges produce the most potent and highly selective bioactive secondary metabolites. These animals (or their associated symbiotic microorganisms) synthesize secondary metabolites whose activity and selectivity has developed during their long evolutionary history. During the course of exploitation of these resources two marine sponges, Fasciospongia cavernosa doc var.brown (dark brown) Fasciospongia cavernosa doc var.yellow (yellow) collected from the visakhapatnam coast of Bay of Bengal were investigated in order to assess the potential of these microorganisms for the production of antimicrobial compounds. The aqueous and organic extracts of both the sponges showed broad spectrum antibiotic activity. In this study a total of 178 microorganisms were isolated from different parts of two sponges and most of them from middle part of the sponge. The isolates were investigated in order to assess the potential of these microorganisms for the production of antimicrobial compounds. Testing for antimicrobial activities were performed against Gram-positive ( Staphylococcus aureus, Bacillus subtilis, Bacillus cereus ) Gram-negative bacteria ( Pseudomonas aeruginosa, Escherichia coli, Proteus vulgaris ), fungi ( Candida albicans, Aspergillus niger ) and 10 pathogenic organisms. Resulting mean diameter of inhibition zones revealed isolates B4 & B6 were the most potent of all the isolates. The present study has revealed the presence of high numbers of diverse culturable microorganisms associated with the marine sponges from Visakhapatnam Coast of Bay of Bengal as well as their potential to produce bioactive metabolites.